SEDIMENTOLOGICAL AND GEOCHEMICAL CHARACTERIZATION OF HOLOCENE SEDIMENTS, FROM ALIKES LAGOON, ZAKYNTHOS ISLAND, WESTERN GREECE - Avramidis, P.; Panagiotaras, D.; Papoulis, D.; Kontopoulos, N. (Bulletin of the Geological Society of Greece, 2010)
The study area is the Alikes wetland (an old salt pan) which is located in the northern part of Zakynthos island. In the Alikes lagoon an exploratory borehole (GA-1) were drilled in a depth up to 21.20m. A total number of forty six (46) samples were analysed for their particle size, calcium carbonate and total organic carbon content. Moreover, bulk sample chemical analyses for major and trace elements were carried out on 12 samples, as well as mineralogical analysis for bulk, oriented and the clay fraction (<2 μm) were determined by powder X-Ray diffraction. The grain size characteristics, statistical parameters and TOC, for the Holocene analysed samples, suggest a coastal environment (restricted-shallow) with reduced salinity such as a lagoon margin and in a tidal flat and/or marsh particularly. Depositional environments and the source material affecting the geochemical signature indicating that that Al, Mg, K are mainly associated with the aluminosilicate fraction of the sediments analyzed, Fe and Ti consistent with detrital phases, while Ca, Si, P, and Mn showing different geochemical patterns.